NALYSIS OF THE "MAN-MACHINE-ENVIRONMENT" SYSTEM'S SAFETY IN COTTON GINNING PRODUCTION (Web of Teachers: Inderscience Research, 2025)
The article presents the results of the analysis of the "human-machine-environment," safety system, and defines the direction of future work on quantitative assessment of injury risk in the cotton ginning industry.